Blockchain-Based Medical Certificate Generation and Verification for IoT-Based Healthcare Systems - Namasudra, Suyel; Sharma, Pratima; González-Crespo, Rubén; Shanmuganathan, Vimal (IEEE Consumer Electronics Magazine, 2023)
Nowadays, medical certificates are very important for many users as they want to avail health benefits like tax purposes, insurance claims, legal procedures, and many more. Generating, issuing, and maintaining medical certificates remain a significant problem; before the invention of the computer, they were available as hard copies. The digitization of medical certificates and documents leads to potential security issues, such as forging of certificates risks the privacy of healthcare documents. Moreover, individuals still need to be physically present and wait at the issuing healthcare centers to get the certificates. Currently, the infrastructure of any healthcare industry connects the Internet of Things (IoT) devices and application software that communicates with the information technology systems. Blockchain technology with IoT can significantly affect the healthcare industry by improving efficiency, security, transparency, and can provide more business opportunities. Therefore, a privacy-preserving technique has been proposed in this article for IoT-based healthcare systems using blockchain technology. The proposed architecture provides an interface between the users and healthcare centers to generate and maintain healthcare documents. Furthermore, the proposed scheme ensures security by specifying rules with a smart contract. Results and discussion show that the proposed scheme is more efficient than the existing schemes.
Keywords: medical services; blockchains; security; public key; medical diagnostic imaging; privacy; computer architecture; electronic health record; integrity; interplanetary file system; gasblocksim; JCR; Scopus